2015
DOI: 10.1186/s13071-015-1272-9
|View full text |Cite
|
Sign up to set email alerts
|

Troglostrongylus brevior in an Eurasian lynx (Lynx lynx) from Bosnia and Herzegovina

Abstract: BackgroundIn the past few years the interest of the scientific community on lungworms of the genus Troglostrongylus has grown due to the increased number of unexpected cases of infections with Troglostrongylus brevior in domestic cats from Mediterranean Europe, likely due to a spill-over from wild reservoirs. Thus, there is a merit to increase our knowledge on the occurrence of this parasite in felids from European regions. The present paper describes lung lesions associated with T. brevior infection in the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 26 publications
(43 reference statements)
0
22
0
Order By: Relevance
“…Then, a hypothesis, T. cati transmitted in wild tigers with a special route including paratenic hosts participating was deduced. Actually, the parasites of wild carnivores take the prey as the paratenic host to spread have been showed [32][33][34], and it Note: * P < 0.1; n/g: the number of eggs/gram faeces is a more reasonable transmission way as the carnivore hosts always have large habits and the oral-faecal transmitting route is impractical in the field. If the speculation we conducted is certified in the future, it will benefit the understanding how T. cati spreads in wild big felines efficiently.…”
Section: Discussionmentioning
confidence: 99%
“…Then, a hypothesis, T. cati transmitted in wild tigers with a special route including paratenic hosts participating was deduced. Actually, the parasites of wild carnivores take the prey as the paratenic host to spread have been showed [32][33][34], and it Note: * P < 0.1; n/g: the number of eggs/gram faeces is a more reasonable transmission way as the carnivore hosts always have large habits and the oral-faecal transmitting route is impractical in the field. If the speculation we conducted is certified in the future, it will benefit the understanding how T. cati spreads in wild big felines efficiently.…”
Section: Discussionmentioning
confidence: 99%
“…Troglostrongylus sp. was described in the twenties (Vevers, 1923) and then neglected until recently, when the rediscovery of this parasite in single European countries such as Spain (Jefferies et al, 2010), Italy (Brianti et al, 2012;, Greece (Diakou et al, 2014) and Bosnia-Herzegovina (Alic et al, 2015) was reported. The adult nematodes of the latter can be easily differentiated from A. abstrusus: Troglostrongylus sp.…”
Section: Introductionmentioning
confidence: 99%
“…Troglostrongylus brevior was described six decades ago in the bronchi of F. s. lybica and F. chaus in Palestine and reported more recently in domestic cats from Spain and Italy [ 3 , 5 , 6 ]. Since then, T. brevior has been found in recent years in domestic cats in Italy [ 7 ], Greece [ 8 ], Bulgaria [ 7 ], Spain [ 9 ], Cyprus [ 10 ], but also in Lynx lynx in Bosnia and Herzegovina [ 11 ]. The two species, T. brevior and Ae.…”
Section: Introductionmentioning
confidence: 99%